Determining the relationships between price and online reputation in lodgings - Manuel Rodríguez-Díaz; Crina Isabel Rodríguez-Voltes; Ana Cristina Rodríguez-Voltes (Administrative Sciences, 2019)
Currently, lodgings' competitiveness depends on pricing, based on the online reputation measured by quantitative scales of variables. The purpose of this article is to analyze the different prices set by lodgings by season in relation to the variables that measure their online reputation. This is an essential aspect in determining prices competitively in a constantly changing market. The study analyzes the offer of three tourist destinations (Gran Canaria and Tenerife in Spain and Agadir in Morocco) and online customer reviews on the quality of service, value, and added value obtained from Booking.com. Bivariate regressions with different functions were carried out to determine which one best matches these variables to the prices. The results show that added value has the greater relationship with prices. The cubic and quadratic functions have the best fit between quality of service and added value with regard to lodging prices. Based on the results obtained, it is possible to determine the most competitive prices lodgings can set depending on the quality of service and the added value offered to customers. To the extent that destinations from different countries are analyzed, the research reaches an international scope that is in line with the competitive reality of the tourism market.
Keywords: 350; tourism destination; online customer review; lodging; price; service quality; added value